On Complete Convergence for Weighted Sums of Arrays of Dependent Random Variables - Soo Hak Sung (Abstract and Applied Analysis)
A rate of complete convergence for weighted sums of arrays of rowwise independent random variables was obtained by Sung and Volodin (2011). In this paper, we extend this result to negatively associated and negatively dependent random variables. Similar results for sequences of φ-mixing and ρ*-mixing random variables are also obtained. Our results improve and generalize the results of Baek et al. (2008), Kuczmaszewska (2009), and Wang et al. (2010).